A study on job related and non-job related stress affecting job performance among nurses / R.Siti Syafiqah Syahmah R.A.Rahaman - R.A.Rahaman, R.Siti Syafiqah Syahmah (2012)
The purpose of this research is to investigate the relationship of job stress that represented by jobs related and non-jobs related stress that affecting job performance among nurses at UKM Kesihatan Sdn. Bhd. The factors of job related stress represent as workload and relationship at work. Meanwhile, the researcher uses personality and work family interaction to represent Independent Variables of non-job related stress. About 38 respondents have been selected among 41 workers to interpret the result in this study. For measuring the independent variable, quantitative method has been selected using questionnaire that were determined through Likert Scale. The finding of the study computed using the statistical package for the social Science (SPSS) version 20. The data analysis was included reliability, descriptive statistics to describe the study sample via mean, median, range, and frequency and correlation. Due to the finding that only one independent variable that shows positive significant relationship affected job performance which is workload. It can be seen by the result of Pearson Correlation Coefficient that shows independent variable is from 3.22 for workload and the rest is less than 2.0 and almost negligible and no significant relationship toward job performance. Several recommendations were given in this research such as increase population and sample size of nurses, add other factors that will affect to the job performance, do testretest method, and add another data collection method.